Evaluation of the physicochemical characteristics of yogurt with probiotic bifidobacterium spp. formulated with uvilla jelly and quinoa flour - Estrella Erazo, Fernanda Milena; Anchundia Lucas, Miguel Ángel; Yambay Vallejo, Wilman Jenny (SATHIRI, 2021)
The practicality, convenience and proximity are sometimes not related to the acquisition of nutritious food products, because the food patterns of certain industries currently contain high percentages of saturated fat, sodium, sugars and calories, for this reason, the consumers today require the markets to offer healthy products of great nutritional value that provide protein, fat, vitamins and minerals to the daily diet. In the present investigation was evaluated of the physicochemical characteristics of yogurt with probiotic Bifidobacterium spp. formulated with uvilla jelly (Physalis peruviana) and quinoa flour (Chenopodium quinoa), as an alternative food. For this, two levels of 25 % and 30 % uvilla jelly were evaluated, and three levels of quinoa flour; 0,6 %, 0,8 % and 1 %, compared to a 0 % control treatment, applying a completely randomized design with AxB factorial procedure. Six formulations were made, the same ones that were sensory evaluated, choosing the T5 treatment (0.8% quinoa flour and 30% uvilla jelly) as the most accepted. As regards the physicochemical characteristics, it was obtained a pH de 4,28; acidity of 0,765 %; total solids content of 23,47 %; protein of 3,23 %; fat of 2,88 %; ash of 0,79 %; fiber of 1,82 %; carbohydrates of 67,81 %; vitamin C of 0,049 %; potassium of 1.245,03 mg/kg and calcium of 738,23 mg/kg; therefore, it is concluded that it is a nutritious and healthy product, suitable for human consumption.
Keywords: Yogurt; quinoa flour; uvilla jelly; probiotic